FIGURATIVE LANGUAGE INWESTLIFE’S SELECTED SONG LYRICS - Elmiara Marbun; Markus Tafonao; Ita Sari Sitorus (LPPM Universitas Darma Agung, 2021)
This research deals with Figurative Language in Westlife's Selected Song Lyrics. The objective of the research was to find out the types of figurative language, to find out the most dominant type of figurative language found in Westlife's song lyrics, and to find out the reasons for the most dominant type of figurative language used in Westlife's Selected Song Lyrics. The data of the study were figurative language found in Westlife's song lyrics. The results of research, there were four types of figurative language used in Westlife's song lyrics, namely: metaphor, simile, personification, hyperbole, with the total data consists of 48 (forty-eight) data with a percentage of 100%. From the total data, metaphor found as many as 12 (twelve) data with percentage (25%), simile found as many as 5 (five) data with percentage (10, 42%), personification found as many as 12 (twelve) data with percentage (25%), hyperbole found as many as 19 (nineteen) data with percentage (39, 58%). Almost all Westlife songs are about love that uses hyperbole so that the language used is perfect, beautiful, easy to understand, and makes things sound more dramatic, especially for couples who are in love.